Software development for the evaluation of the lightning protection system design - Ramalingam, Raveen Kumar (2014)
Due to the high lightning activity in Malaysia, a good and robust lightning protection system (LPS) is required and this system has to be evaluated based on actual influencing parameters. This work describes the development and results of a computer based software for the evaluation of lightning occurrences on a structure. Lightning Protection System Design is a software that allows designers to design a lightning protection system for a particular building or structure. The work discusses on the relevant algorithms to compute the lightning strike probability on a given structure. The program was written in Python and a very simple guided user interface using Visual Basic.NET. It also provides the flow chart in designing and computing the protection system. The software is based on 3 dimensional modeling implementing the electro geometrical model of lightning stroke on the structures that requires protection. The work also evaluates different building structure with different protection levels to calculate the probability of lightning strike.